Laser Interstitial Thermal Therapy to the Posterior Fossa: Challenges and Nuances. (1st September 2019) - Traylor, Jeffrey I; Patel, Rajan; Muir, Matthew; Habib, Ahmed; Bastos, Dhiego Chaves de Almeida; Rao, Ganesh; Prabhu, Sujit S
Abstract: INTRODUCTION: Posterior fossa tumors are rare in adults and pose a challenge to treat due to the bony contour of the posterior fossa, complex anatomical structures including deep venous sinuses, and the proximity of the fourth ventricle and brain stem. We describe our experience with laser interstitial thermal therapy (LITT) for the management of brain metastases and radiation necrosis of the posterior fossa. METHODS: We retrospectively analyzed 13 patients with metastases and radiation necrosis of the posterior fossa managed with LITT. Patient data were extracted from the electronic medical record along with magnetic resonance images (MRI) preoperatively, immediately postoperatively, and at each follow-up. RESULTS: Thirteen patients with histopathologically confirmed radiation necrosis (n = 5) and metastases (n = 8) of the posterior fossa underwent LITT. The median preoperative tumor and postoperative ablation cavity volume was 4.66 and 6.29 cm 3, respectively. The median volume of the ablation cavity decreased to 2.90 cm 3 at 9-mo follow-up. The median volume of peritumoral edema was 12.25 cm 3, which fell to a median 5.77 cm 3 at 1-mo follow-up. Median progression-free survival was 7 mo (range 3-14 mo) from LITT. The mean overall survival (OS) was 40 months (range 2-49 mo). There were no intraoperative complications. One patient experienced palsy of the seventh and eighth cranial nerves on follow-up, attributable to LITT. Two patients received 2 LITT treatments for their respective lesions. CONCLUSION: Lesions of the posterior fossa are challenging to treat given their proximity to the dura and venous sinuses. We demonstrate that LITT ablation may be a safe and feasible option for metastases and radiation necrosis of the posterior fossa. Larger studies are needed to confirm the efficacy of this approach.